Na lida do Policial Civil: estudo sobre as estratégias de formação continuada de policiais civis para o atendimento aos grupos vulneráveis - Barbara Aragao Teodoro Silva (2014)
The following study aims to discuss the learning strategies of education and improvement courses of Civil Police of Minas Gerais State (Polícia Civil de Minas Gerais PCMG) after the insertion into the professional institution, specifically in the Womens Police Station (Delegacia Especializada de Atendimento à Mulher DEAM). It aims to identify, from the perspective of the subjects, the conditioning aspects - motivations and strategies - that influence the choices in professional development and education maintenance. For this, it was considered the relationship between the micropolitical aspects of police organization and the macrostructural determinations, result of historical context of public policy formulations. Methodologically, the study was developed with a qualitative approach, with the data acquisition divided in three moments: survey of institutional data related to continuing education courses; a questionnaire application to civil police officers of DEAM; individual interview with officers of that police unit. The data were processed by softwares and then they were triangulated, allowing the understanding of the investigated context and a possible replication of the study in other police stations realities. The results showed the police organizations as places differentiated by their micropolitics, in which the conflict and processes to maximize power and interests have the key role in making professional profile and, consequently, in police officers continuing education. Also, the influences of gender relations in the structuring of institutional and professional hierarchies were identified, as well as in dealing and valuation of crimes against women. Furthermore, were highlighted aspects concerning anguish and institutional precariousness, pointing to the need of rethinking the educational models and professional valorization offered by the institution and the positioning of the feminine before patriarchal models of procedures.